Triclosan affects axon formation in the neural development stages of zebrafish embryos (Danio rerio). (May 2018) - Kim, Jin; Oh, Hanseul; Ryu, Bokyeong; Kim, Ukjin; Lee, Ji Min; Jung, Cho-Rok; Kim, C-yoon; Park, Jae-Hak
Abstract: Triclosan (TCS) is an organic compound with a wide range of antibiotic activity and has been widely used in items ranging from hygiene products to cosmetics; however, recent studies suggest that it has several adverse effects. In particular, TCS can be passed to both fetus and infants, and while some evidence suggests in vitro neurotoxicity, there are currently few studies concerning the mechanisms of TCS-induced developmental neurotoxicity. Therefore, this study aimed to clarify the effect of TCS on neural development using zebrafish models, by analyzing the morphological changes, the alterations observed in fluorescence using HuC-GFP and Olig2-dsRED transgenic zebrafish models, and neurodevelopmental gene expression. TCS exposure decreased the body length, head size, and eye size in a concentration-dependent manner in zebrafish embryos. It increased apoptosis in the central nervous system (CNS) and particularly affected the structure of the CNS, resulting in decreased synaptic density and shortened axon length. In addition, it significantly up-regulated the expression of genes related to axon extension and synapse formation such as α1-Tubulin and Gap43, while decreasing Gfap and Mbp related to axon guidance, myelination and maintenance. Collectively, these changes indicate that exposure to TCS during neurodevelopment, especially during axonogenesis, is toxic. This is the first study to demonstrate the toxicity of TCS during neurogenesis, and suggests a possible mechanism underlying the neurotoxic effects of TCS in developing vertebrates. Graphical abstract: Image 1 Highlights: TCS changes craniofacial morphology and neural structures in zebrafish embryos. TCS affects the expression of apoptosis and neurogenesis related genes. TCS is toxic to neurodevelopmental stages, especially in axonogenesis. This is the first study to confirm the developmental neurotoxicity of TCS. Abstract : This study first identifies potential mechanisms of developmental neurotoxicity that can occur when the organic compound triclosan is transmitted to developing vertebrate embryos.